The Story of Garum : Fermented Fish Sauce and Salted Fish in the Ancient World - Grainger, Sally (Taylor & Francis Group, 2020)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Contents -- List of Figures -- List of Tables -- Preface and Acknowledgments -- Introduction -- 1. Fish Sauce in Classical Literature -- 2. Fish Sauce in the Consumption Literature: A Literary and Archaeological Chronology -- 3. Fish Sauce in Culinary, Medical, and Veterinary Sources -- 4. Fish Sauce from Papyri in Greek Speaking Egypt -- 5. Fish Sauce in the Late Roman, Byzantine and Early Medieval World -- 6. Fish Sauce from an Archaeological Perspective -- 7. Fermented Fish Sauce in Southeast Asia -- 8. Modern Fish Sauce Experiments -- 9. Fishing in the Mediterranean -- 10. The Infrastructure of Fish Sauce Manufacture -- 11. Fish Bones as Evidence of Sauce and Salsamenta -- 12. Fish Sauce Amphorae as Functional Vessels -- Afterword -- Bibliography -- Index.